TOE1 deadenylase inhibits gastric cancer cell proliferation by regulating cell cycle progression - Sun, Xiao-Lin; Song, Huan-Xi; Li, Jia-Hui; Liu, Yi-Jin; Wang, Xin-Ya; Zhang, Li-Na (Biochimica et biophysica acta. General subjects, 2025)
TOE1, also known as hCaf1z, belongs to the DEDD superfamily of deadenylases and a newly identified isoenzyme of hCaf1 deadenylases. Previous research has demonstrated that TOE1 has deadenylase activity, which can catalyze the degradation of poly(A) substrates and interact with hCcr4d to form the unconventional human Ccr4-Caf1 deadenylase complex. Our recent research indicates that hCaf1a and hCaf1b isoenzymes, highly expressed in gastric cancer, promote gastric cancer cell proliferation and tumorigenicity via modulating cell cycle progression. However, no studies have yet explored the relationship between TOE1 deadenylase and tumor development. In our study, we systematically investigated the functions and mechanisms of TOE1 in gastric cancer progression. Our findings revealed that overexpression of TOE1 inhibited gastric cancer cell proliferation, invasion and migration, promoted cell apoptosis, and led to cell cycle arrest in G0/G1 phase, while TOE1 knockdown had the opposite biological effects on these processes in gastric cancer cells. Further results indicated that TOE1 suppressed gastric cancer progression by inhibiting EMT process and MMPs expression. Moreover, our study clarified that TOE1 blocked gastric cancer cell cycle progression by up-regulating the expression level of the key cell cycle factors p21 and p53 through different regulatory mechanisms. Specifically, TOE1 up-regulated p53 expression by enhancing p53 promoter activity, and up-regulated p21 expression by enhancing p21 mRNA stability. Collectively, our findings first contribute to further elucidating the molecular mechanisms by which TOE1 participates in the regulation of gastric cancer progression, and are expected to provide a theoretical basis for diagnosis and targeted treatment of gastric cancer. •TOE1 inhibited gastric cancer cell proliferation, invasion and migration bysuppressing EMT process and MMPs expression.•TOE1 blocked gastric cancer cell cycle by up-regulating the expression of cell cycle-regulated factors p21 and p53.•TOE1 may function as a novel tumor suppressor gene in gastric cancer progression.